"Un nuevo saltasaurino (Sauropoda, Titanosauridae) de la provincia de Río Negro (Formación Allen, Cretácico Superior), Patagonia, Argentina" (Ameghiniana, 2014)
"A new saltasaurine taxon based on a femur,pelvic bones and dorsal and caudal vertebrae is described. The closest relationships of the new taxonare with Saitasaurus loricatus Bonaparte and Powell from northwestem Argentina. These species share caudalvertebrae bearing a ventral depression divided by a longitudinal septum. The record of Saltasaurinaeis thus limited to the Upper Cretaceous of Argentina, with three distinct taxa: Saliasaurus loricatus,Neuquensaurus ausiralis Lyddeker and Rocasaurus muniozi n. gen., n. sp."